Exploring the differential functions of circulating follicular helper T and peripheral helper T cells in rheumatoid arthritis based on metabolism patterns - Bai, Ziran; Yang, Siwen; Ren, Jinyi; Zhang, Cheng; Chen, Xianmei; Huang, Huina; Wang, Guan; Tang, Yawei; Qi, Jingjing; Li, Xia (Frontiers in Immunology, 2025)
IntroductionThe number of circulating follicular helper T (cTfh) and peripheral helper T (Tph) cells is elevated in rheumatoid arthritis (RA), yet the molecular mechanisms mediating their specific contributions to RA pathology remain unclear. In this study, we explored the distinct function of cTfh and Tph cells based on metabolism patterns in RA.MethodsPeripheral CD4+ T cells from RA patients were treated with CXCL13 or CCL2, glycolysis inhibitor 2-DG or mitochondria-targeted antioxidant MitoQ in vitro. Collagen induced arthritis (CIA) mice were treated with 2-DG or MitoQ in vivo. The frequency, transcription factors, functional molecules, cellular senescence, glycolytic activity and mitochondrial ROS (mtROS) of cTfh and Tph cells were assessed. Joint inflammation, CD4+PD-1+ T cells, glycolytic enzymes or IL-1β and IL-6 in ankle joints of CIA mice were detected.ResultsWe found that in RA patients, in comparison with Tph cells, cTfh cells show higher levels of Bcl6 and BATF, B helper-related molecules, and glycolytic activity. While Tph cells exhibit higher levels of Blimp1 and T-bet, cytotoxicity-related molecules and mtROS, and more significant cellular senescence characteristics. In addition, CXCL13, the ligand for CXCR5, increases the expression of key glycolytic enzymes in RA cTfh cells, while CCL2 increases mtROS in RA Tph cells. 2-DG reduces the expression of B helper-related molecules cells, and MitoQ mitigates cytotoxic activity of cTfh and Tph cells. Both treatments ameliorate RA symptoms and decrease the number of cTfh and Tph cells in CIA mice.ConclusionOur study suggests that in RA patients, cTfh cells display a more robust B helper-associated function, potentially linked to the CXCL13-CXCR5 axis enhancing glycolysis. Tph cells, on the other hand, show greater cytotoxic activity, possibly due to the CCL2-CCR2 axis increasing mtROS production. Targeting glycolysis or mtROS may offer a novel therapeutic strategy for RA patients.